Gambaran Kejadian Ikutan Pasca Imunisasi (KIPI) Setelah Melakukan Vaksinasi Covid-19 Pada Masyarakat Banjarmasin Selatan - Darini Kurniawati; Iwan Yuwindry; Sariyasih Sariyasih (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
ABSTRACT Background : Covid-19 attacks the respiratory tract which first appeared in December 2019 in Wuhan City, Hubei Province, China. The World Health Organization (WHO) has declared it as a global pandemic since March 11, 2020. The COVID-19 vaccination program in Indonesia has started on January 13, 2021. Covid-19 vaccination can cause Post Immunization Adverse Events (AEFI) which can be characterized by mild to moderate symptoms. heavy. Objective : To find how to follow-up events after immunization (KIPI) in the people of southern Banjarmasin after the Covid-19 vaccination. Methods : This research is an observational quantitative research with descriptive research type, this research only describes an object of research, then the research data obtained in the form of numbers will be qualitatively obtained so that the results obtained can be described. This research was conducted using the naranjo algorithm which was distributed to the public and input via Google Form. Results : This study shows that 37 respondents with a percentage of men 51% and women 49% obtained a score of 4-8, namely "Most likely Terjasi ROM" with a total of 13 respondents, who used the Sinovac vaccine in 11 respondents and there were 2 moderna respondents. then with a score of 1-3, namely "Probability of ROM" with a total of 23 respondents who used the Sinovac vaccine. Then with a score of 0 which is "it is doubtful that ROM will occur" there are as many as 1 respondent with the Sinovac vaccine. Of the two vaccines, the Sinovac vaccine has an effectiveness of 56-65% while the Modena vaccine has an effectiveness of 94.1%. The common side effects of the Sinovac vaccine include injection pain, fever, fatigue, while the most common side effects of the moderna vaccine are fever, pain on injection, headache, and nausea. Conclusion : it can be concluded that Post-Immunization Adverse Events (AEFI) of respondents who vaccinated against covid-19 were 23 respondents in the Possible category, 13 respondents in the Probable category, and 1 respondent in the Doubtful category.